2018
DOI: 10.1007/s12185-018-2424-4
|View full text |Cite|
|
Sign up to set email alerts
|

Atypical erythroblastosis in a patient with Diamond–Blackfan anemia who developed del(20q) myelodysplasia

Abstract: Diamond-Blackfan anemia (DBA) is a congenital red cell aplasia arising from ribosomal protein (RP) defects. Affected patients present with neonatal anemia, occasional dysmorphism, and cancer predisposition. An anemic newborn was diagnosed with DBA due to RPL5 mutation (c.473_474del, p.K158SfsX26). Refractory anemia required regular transfusions and iron chelation therapy. Pancytopenia occurred at age 16 years. Bone-marrow studies showed myelodysplasia, erythroblastosis, and clonal evolution of del(20)(q11.2q13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Mutations in human HMGCS1 have not been associated with disease, but there are 8 congenital anomalies that occur as a consequence of mutations within other enzymes of the CSP. [5][6][7][8][9][10][11]13,51 These congenital anomalies are characterized by diverse phenotypes, 7,21,[51][52][53] and mutations in the zebrafish hmgcs1 gene mimic these disorders, resulting in a multiple congenital anomaly syndrome. Therefore, zebrafish with mutations in hmgcs1 have the potential to reveal novel cellular and molecular mechanisms underlying individual phenotypes across multiple genetic disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in human HMGCS1 have not been associated with disease, but there are 8 congenital anomalies that occur as a consequence of mutations within other enzymes of the CSP. [5][6][7][8][9][10][11]13,51 These congenital anomalies are characterized by diverse phenotypes, 7,21,[51][52][53] and mutations in the zebrafish hmgcs1 gene mimic these disorders, resulting in a multiple congenital anomaly syndrome. Therefore, zebrafish with mutations in hmgcs1 have the potential to reveal novel cellular and molecular mechanisms underlying individual phenotypes across multiple genetic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Diamond-Blackfan anemia can result from mutations in the transcription factor GATA1. [12][13][14] GATA1 is the founding member of the GATA family of zinc finger transcription factors 15 that interacts with a multitude of other proteins such as Friend of GATA, EKLF, SP1, p300, and PU.1 to promote erythropoiesis. 16 Cholesterol is 1 known regulator of RBC function because it maintains the structure and integrity of the RBC membrane and aids in the protection against oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Here we show that cholesterol and isoprenoids regulate erythropoiesis using a zebrafish harboring mutations in the hmgcs1 gene (Vu57 allele). Mutations in human HMGCS1 have not been associated with disease, but there are 8 congenital anomalies that occur as a consequence of mutations within other enzymes of the CSP [5][6][7][8][9][10][11]13,48 . These congenital anomalies are characterized by diverse phenotypes 7,21,[48][49][50] and mutations in the zebrafish hmgcs1 gene mimics these disorders resulting in a multiple congenital anomaly syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic disorders of RBCs have revealed critical mediators of erythropoiesis [7][8][9][10][11] , many of which include transcription factors. For example, Diamond-Blackfan anemia can result from mutations in the transcription factor GATA1 [12][13][14] . GATA1 is the founding member of the GATA family of zinc finger transcription factors 15 and interacts with a multitude of other proteins such as Friend of GATA (FOG), EKLF, SP1, p300 and PU.1 to promote erythropoiesis 16 .…”
Section: Introductionmentioning
confidence: 99%
“…However, hematologists continue to face difficulties in the diagnosis of patients with atypical DBA when both ADA activity and RP gene tests show normal results. In our previous study, we demonstrated that GSH was a novel biomarker of DBA(Utsugisawa et al 2016;Ichimura et al 2017;Noguchi et al 2017;Sonoda et al 2018). Hence, the…”
mentioning
confidence: 98%